Effects of Density Control and Fertilization on Log Wood Quality from a Douglas-fir Stand in Western Oregon, USA. Issue 2 (26th November 2019) - Kantavichai, Rapeepan; Turnblom, Eric C; Lowell, Eini C
Abstract: This study aimed to investigate the effects of juvenile spacing (precommercial thinning), thinning, and fertilization on Douglas-fir butt log (first 4.9 m) and second log (4.9–10 m) quality attributes: juvenile wood percentage, heartwood percentage, rings per inch, specific gravity, and modulus of elasticity. A 41-year-old, 36.6 m site index Douglas-fir stand in western Oregon, USA was selected as the first stand to explore. Nine common silviculture pathway treatments of juvenile spacing, thinning, and fertilization were applied to independent 0.404-hectare plots. Ninety-nine trees were felled and disks cut at five heights along the stem. Wood properties were measured and calculated from the disks for log quality attributes. There was no effect of silvicultural treatments on log heartwood percentage, but significant effects on other log quality attributes were observed. Juvenile wood percentage and rings per inch declined with stand density control and fertilization treatment. Responses to thinning and fertilization in log specific gravity depend on juvenile spacing. Also, thinning and juvenile spacing were shown to have impacts on log modulus of elasticity.